Morphometric Analysis of Tentorial Orifice and its Anatomical Variations as Relevant to Transtentorial Herniation: A Preliminary Cadaveric Study - Sharma, Diksha; Kaul, Rakshay; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
The tentorial orifice is a space in the tentorium cerebelli that lies toward the center and anteriorly related to the brainstem, cranial nerves, cerebrum, and cerebellum. The tentorium cerebelli is a fold of the dura mater that separates the supratentorial and infratentorial chambers. The anatomy of the tentorial orifice is complex in morphology, and it has a great significance in the neurosurgical field. Detailed understanding of the anatomical variations in the tentorial notch may help find the progression and clinical aspects of transtentorial herniation.The aim of the study was to investigate the morphometric characteristics of the tentorial notch and its anatomical variations in human cadavers.The study was conducted on 20 human cadavers, aged 20 to 74 years, after the conventional autopsy procedure within 24 hours after death, followed by sectioning of the midbrain at the level of the tentorial edge to note the respective observations, which were the following: (1) maximum notch length (MNL), the length between the apex of the notch and the posterosuperior edge of the dorsum sellae; (2) maximum notch width (MNW) and maximum width of the tentorial notch; (3) interpedunculoclival distance, the distance between the posterosuperior edge of the dorsum sellae and the interpeduncular fossa; (4) apicotectal distance, the distance from the apex of the notch to the tectum of midbrain; and (5) anterior notch width, the width of the tentorial notch in the axial plane through the dorsum sellae posterior aspect. The tentorial notch is classified into eight types by using two variables, which are MNL and MNW. The data obtained were analyzed.Twenty autopsy cases, comprising 18 males and 2 females, were included in the study. The groups defined by MNW (mean: 29.12 ± 1.88 mm [range: 24.4–34.3]) were labeled as narrow, midrange, and wide. Other groups defined by MNL (mean: 52.13 ± 5.01 mm [range: 44.2–59.92 mm]) were labeled as short, midrange, and long.Anatomical variability in the morphology of the tentorial aperture may be associated in various clinical scenarios related to transtentorial herniation and other traumatic brain injuries. This preliminary study provides a guideline to plan the trajectory during neurosurgical procedures to be performed in the vicinity of the tentorial aperture.
Keywords: transtentorial herniation; tentorium cerebelli; brainstem herniation; notch classification; cadaveric study